The Effect of WTI Prices and the Fed’s Rates on the JCI During the Covid-19 Pandemic - Aji Prasetyo Suyono; Muhammad Miqdad; Mohammad Imam Farisi (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2022)
As a source of funding in the industrial world and also as a forum for people who want to carry out investment activities, the capital market has a vital function in national development. This research is a quantitative research using logistic regression analysis model (Logit). This study uses two independent variables and one dependent variable in the form of a dummy variable on a nominal scale, which will be estimated using the T statistical test method. The results of SPSS output calculations using the T statistical test conclude that World Oil Prices and The Fed Interest Rate partially have no effect on the volatility of the Jakarta Composite Index (JCI) during the Covid-19 Pandemic. Each of these independent variables is not a good indicator for estimating the movement of the JCI during the Covid-19 pandemic and investors should not use it as the basis for making investment decisions in the stock market